Patterns of SAC Utilization and The Sine Qua Non of The Self-propelled Development Of Students English Proficiency - Furaidah Furaidah,; Suharmanto Suharmanto (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
This article reports on a study intended to find out the patterns of the Self Access Center (SAC) utilization by students of the English Departments, State University of Malang, and to explore the most effective pattern in developing studentsÃ¢â¬â¢ English proficiency as well as studentsÃ¢â¬â¢ learning autonomy. The study involved 207 students of various years. The data were collected through questionnaires, observations, and interviews. Analyses of the studentsÃ¢â¬â¢ responses to the questionnaires resulted in the findings that the more advanced the students were, the less frequently they utilized the SAC; that the studentsÃ¢â¬â¢ proficiency was improving along with classes; and that the students were autonomous in their learning. In addition, the study also found out that the materials and activities need to be periodically updated in order for the SAC to better serve the learning needs of the more advanced students.